Effect of rosemary and sage extracts on frying performance of refined, bleached and deodorized (RBD) palm olein during deep-fat frying - Che Man, Yaakob; Jaswir, Irwandi (Elsevier, 2000)
The effects of two natural antioxidants, rosemary and sage extracts, on physico-chemical changes of refined, bleached and deodorized (RBD) palm during deep-fat frying and on sensory acceptability of potato crisps were studied. Results showed that the two antioxidants significantly (P<0.05) retarded the oil deterioration during 6-day frying. The two antioxidants were proven to lower the rate of oxidation of oils during frying. It was also shown that, during frying, the quality of oils gradually decreased. Sensory evaluation indicated that, except for crispiness scores, both rosemary and sage extracts could improve acceptability of fried potato crisps. However, no sample was unacceptable by panellists even up to day 6. In general, sage extract was as effective as rosemary extract in maintaining the quality of oils during frying.